STUDENTS’ ABILITY IN IMPLEMENTING SCIENTIFIC APPROACH IN WRITING COURSE DESIGN - Afriyanti, Rika (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2018)
This research deals with the student’s ability in implementing Scientific Approach Steps in Curriculum Subject. Some students think that writing course design based on The Curriculum 2013 are not easy, because the course design involve five stages of teaching activities, they are observing, questioning, experimenting, associating, and communicating. Therefore, the researcher wants to know the students’ ability in implementing those steps in writing course design for curriculum subject. To get the answer, the researcher conducted qualitative research and collected the students’ course design as the data. There were 25 course designs used as the data and then, the researcher classified the students’ ability in implementing those steps into four categories. They are very good implementation, good implementation, poor implementation and very poor implementation. After analyzing the data the researcher found that 12 students belong to good ability in implementing the Scientific steps, 8 students belong to poor implementation and 5 students belong to very poor implementation. Meanwhile no students belong to very good implementation. This result means that the 12 students have understood about the format, but they still have little bit problem in developing each of the step. Meanwhile, 8 students understood about the format, but they were difficult to develop the content and 5 students did not understand the format and also how to develop the content. Shortly, 13 students still need information and direction about implementing the scientific approach based on The Curriculum 2013.Keywords: Students’ Ability, Scientific Approcah, Course Design.